Description of the Assistance Function the Keluarga Harapan Program (PKH) at Balai Betung Payakumbuh - Riza Novri Yanti; Ismaniar Ismaniar (Universitas Negeri Padang, 2019)
This study background is the success of the Program Keluarga Harapan (PKH) at Balai Betung Payakumbuh. This is proved by the decreasing of Drop Out students, the increasing of the toddler nutrition’s quality, and the decreasing of PKH’s member. This study supposes the impact of the Assistance Function in the Program Keluarga Harapan (PKH). This study goal is to observe the description of assistance function in the PKH’s members at Balai Betung Payakumbuh. The type of this study is quantitative descriptive. The population in this study is all of PKH’s members that are 25 persons. The technique sample of this study is cluster random sampling. The sample is 82% of the population is about 20 persons. The data collecting is using a questionnaire. The data collection tool is a list of statements. The data analysis technique is using a percentage formula. The study result shows the Assistance Function based on the PKH’S member's statement are a) problem-solving consultations in PKH’s activities carried out well. b) the Assistance Function as source management during PKH’s activities carried out well. c) the Assistance Function as an educator in the PKH’S activities carried out well. These show by the members of PKH’s answered often. Based on the study the assistance function suggested to be continued ideally and maintain the activities that have done.Keywords: Function, Assistance, Success, Program